2019
DOI: 10.33882/jida.13.25186
|View full text |Cite
|
Sign up to set email alerts
|

CONSULTANCY IN ORAL PATHOLOGY: CURRENT SCENARIO & FUTURE SCOPE IN INDIA- A Survey Based Study

Abstract: BACKGROUND- Department of Oral Pathology provides a routine diagnostic pathology service for their associated dental hospitals and a specialist referral service for general histopathologists who may be confronted with unfamiliar lesions in the head ,neck and face regions.Despite literature that have stressed the importance of oral pathology services, there is not much published data on the use of such services by general histopathologists. AIM- The purpose of this study was to determine the extent to which i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Mudaliar et al in India (Mumbai), on the other hand, have reported lower percentages for the same in their study. [ 3 4 5 ] These differences, as highlighted by studies, could be due to differences in the training methods and curriculum related to the specialty of oral pathology. Hence, generating interest among the students toward the specialty by implementing new ideas in the curriculum in a constructive manner is needed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mudaliar et al in India (Mumbai), on the other hand, have reported lower percentages for the same in their study. [ 3 4 5 ] These differences, as highlighted by studies, could be due to differences in the training methods and curriculum related to the specialty of oral pathology. Hence, generating interest among the students toward the specialty by implementing new ideas in the curriculum in a constructive manner is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, generating interest among the students toward the specialty by implementing new ideas in the curriculum in a constructive manner is needed. [ 5 6 ] The oral specimen formed a small proportion of the total specimen received in all previous studies, which could be one reason for low referral rates by general pathologists. The use of a common reference book called “Shafer's textbook of Oral Pathology,” by general and oral pathologists in our survey to diagnose head and neck pathologies, could be another reason for low referrals by general pathologists.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study's findings contribute to our understanding of the recognition and acknowledgment of oral pathology expertise among general pathologists, emphasizing the value of collaboration between general pathologists and oral pathologists in providing comprehensive care for patients with oral pathological conditions. Contrarily, a study conducted by Uma Mudaliar et al 13 reported a low level of awareness of oral pathology in their study, indicating the need for interventions to improve the knowledge and understanding of oral pathology among general pathologists. The findings of this study provide strong support for the belief held by many general pathologists regarding the importance of oral pathologists in the diagnosis of oral pathological lesions.…”
Section: Discussionmentioning
confidence: 84%